Effect of calcination cycles on the preparation of tin oxide based traditional drug: studies on its formation and characterization - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Gaikwad, A. B.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2006)
The preparation method of metal based Indian traditional drugs involves conversion of a pure metal into its oxide by repeated high temperature calcination cycles. In this work, the effect of number of calcination cycles followed in the preparation of tin oxide based Ayurvedic drug, `vanga bhasma' was studied by a systematic characterization of the drug samples after various calcination stages. It was found that tin was in the form of Sn4+ state and that the formation of SnO2 proceeded step-wise through Sn(OH)(4). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: calcination cycles; Oxidation; oxidation state of tin; Particle size; tin oxide; vanga bhasma

Enhanced solar-radiation induced photocatalytic activity of surface-modified nanocrystalline anatase-titania - Priya, R.; Baiju, K. V.; Shukla, S.; Biju, S.; Reddy, M. L. P.; Patil, K. R.; Warrier, K. G. K. (Catalysis Letters, 2009)
Sol-gel derived pure nanocrystalline (similar to 20-30 nm) anatase-titania has been surface-modified by depositing silver(I) oxide and silver (predominantly the former) via UV-reduction process. The pure and surface-modified nanocrystalline anatase-titania have been characterized using different analytical techniques for determining the average nanocrystallite size, phase-contents, surface-chemistry, as well as the absorption and photoluminescence characteristics. It is demonstrated that, the latter exhibits an enhanced solar-radiation induced photocatalytic activity as compared to that of the former as a result of the absorption in the visible-region and enhanced photo-induced e(-)/h(+) life-time, both caused by the surface-deposition of silver(I) oxide and silver.
Keywords: Nanocrystalline; Photocatalysis; Silver; sol-gel; titania; UV-reduction

Effect of leakage current and dielectric constant on single and double layer oxides in MOS structure - Laha, Pinaki; Panda, A. B.; Dahiwale, S.; Date, Kalyani S.; Patil, K. R.; Barhai, P. K.; Das, A. K.; Banerjee, Indrani; Mahapatra, S. K. (Thin Solid Films, 2010)
MOS structure of Al/Al2O3/n-Si, Al/TiO2/n-Si and Al/Al2O3/TiO2/n-Si was obtained by deposition of Al2O3 and TiO2 on silicon substrate by RF Magnetron Sputtering system. The total thickness of the oxide layer similar to 40 +/- 5 nm in the MOS structure was kept constant. Samples were characterized by X-Ray diffraction (XRD). X-Ray photoelectron spectroscopy (XPS), Impedance analyzer and Current-voltage (J-V) characteristics. The variations in the dielectric constant and tan 8 of the MOS capacitor in the frequency range of 1000Hz-1MHz were measured by impedance analyzer. The variation in dielectric constant of the Al/Al2O3/TiO2/n-Si multilayer compared to single layer of Al/Al2O3/n-Si and Al/TiO2/n-Si is due to high probability of defects, lattice mismatch and interface interactions. The steep rise of Tan 6 values in the Al/Al2O3/TiO2/n-Si structure is due to the resonance effect of both Al2O3 and TiO2 layers. The leakage current mechanisms of MOS structures were extracted from Schottky coefficient and Poole-Frenkel coefficient. Theoretical values of Schottky coefficients (beta(SC)) and Poole-Frenkel coefficients (beta(PF)) for each sample were estimated using the real part of the dielectric constant. The experimental values were calculated from J-V characteristics and compared with theoretical values. The appropriate model has been proposed. It was found that Schottky and Poole-Frenkel mechanisms are applicable at low and high field respectively for all MOS structures. The combination of Al/Al2O3/TiO2/n-Si is found to be a promising structure with high dielectric constant and low leakage current suitable for MOS devices. (C) 2010 Elsevier B.V. All rights reserved.
37th International Conference on Metallurgical Coatings and Thin Films, San Diego, CA, APR 26-30, 2010
Keywords: Al2O3; dielectric constant; Leakage current; MOS device; Poole-Frenkel emission; Schottky emission; TiO2

Effect of preparation parameters of Cu catalysts on their physico-chemical properties and activities for glycerol hydrogenolysis - Mane, R. B.; Kondawar, S. E.; Niphadkar, P. S.; Joshi, P. N.; Patil, K. R.; Rode, C. V. (Catalysis Today, 2012)
Cu based catalysts were prepared by co-precipitation, alkali fusion followed by precipitation and direct solid state fusion methods. The changes in the phase formation, morphology, crystallite size, extent of aggregation, strength and nature of acid sites were observed due to variations in precipitating agents and also their order of addition. The catalyst prepared by co-precipitation using Na2CO3 showed the predominant presence of metallic Cu phase with a crystallite size of 5 nm, well segregated spherical morphology and highest acidity in the activated sample. These intrinsic properties contributed to achieve the highest glycerol conversion of 62% and 1,2-PDO selectivity of 88% in glycerol hydrogenolysis. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Co-precipitation; Cu catalysts; Glycerol hydrogenolysis; Physico-chemical properties; Solid state fusion

Effect of preparation parameters on characterization and activity of Co3O4 catalyst in liquid phase oxidation of lignin model substrates - Mate, Vivek R.; Jha, Ajay; Joshi, U. D.; Patil, K. R.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2014)
The nano structured spinel cobalt oxide (Co3O4) was prepared via simple co-precipitation method and its catalytic activity was evaluated for the liquid phase aerobic oxidation of lignin sub structure compounds such as veratryl alcohol. Catalyst preparation parameters influenced its morphology eventually affecting its oxidation activity. Thus, nano rod shaped CO3O4 catalyst showed 75% and 38% conversion of veratryl alcohol with complete selectivity to veratryl aldehyde in toluene and water, respectively, under base free condition. The influence of reaction conditions, such as temperature, oxygen pressure and catalyst loading was studied to obtain the optimum product yield and selectivity to the desired product. Furthermore, oxidation of various sub-structures of lignin model compounds was also studied over the same catalyst which was found to be in the following order: secondary alcohol >di-substituted > tri-substituted > monosubstituted > non-substitution. The stability of the catalyst was confirmed by its successful recycle for three times. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Coniferyl alcohol; Nano Co3O4; Sinapyl alcohol; TPR; Veratryl alcohol